A novel approach to management of sleep-associated problems in patients with breast cancer (MOSAIC) during chemotherapy : A pilot study. Issue 10 (10th April 2020) - Palesh, Oxana; Solomon, Natalie; Hofmeister, Elisa; Jo, Booil; Shen, Hanyang; Cassidy-Eagle, Erin; Innominato, Pasquale F; Mustian, Karen; Kesler, Shelli
Abstract: Study Objectives: This pilot randomized controlled trial (RCT) was conducted to assess the preliminary effects of Brief Behavioral Therapy for Cancer-Related Insomnia (BBT-CI) delivered by trained research staff in comparison to a sleep hygiene pamphlet control and to assess moderators of treatment effect in patients with breast cancer undergoing chemotherapy. Methods: Of 74 participants recruited, 37 were randomized to BBT-CI and 37 were randomized to the control condition. Trained staff members delivered the intervention during chemotherapy treatments to reduce patients' burden. Insomnia was assessed with the Insomnia Severity Index (ISI), anxiety was assessed with the Spielberger State-Trait Anxiety Inventory, symptom burden was assessed with the Symptom Inventory (SI), and study staff recorded previous treatments and surgeries received by patients. Results: Patients randomized to BBT-CI showed significantly greater improvements in their ISI scores compared to the sleep hygiene group. Additionally, several treatment moderators were identified. The effect of BBT-CI was greater among individuals with lower baseline state-trait anxiety, with previous surgery for cancer, and with higher baseline somatic symptom severity. Conclusions: BBT-CI shows preliminary efficacy compared to the sleep hygiene handout on insomnia in cancer patients undergoing chemotherapy. A large-phase III RCT needs to be conducted to replicate the preliminary findings.